Beauty does not always denote danger: aposematic syndrome in the poison frog Dendrobates auratus (2011)
Warning signals modify predators foraging behavior by promoting the association between conspicuous signals (often coloration) and prey's unpalatability. This ecological strategy, aposematism, is better studied as a phenotypic syndrome because it involves covarying physiological, life history and behavioral traits. Among dendrobatid frogs, aposematic coloration has independently evolved in several lineages and, to the interspecific level, appears correlated with diet specialization, toxicity, body size and metabolic rate. The occurrence of intraspecific variation in coloration renders them excellent study systems to understand the evolutionary mechanisms underlying the very origin of aposematism. In this study we aimed to test the hypothesis that geographic divergence in Dendrobates auratus' aposematic coloration is correlated with toxicity, diet specialization, body size and jumping performance. We studied between 7-13 individuals from each of nine localities in Panama and found significant geographic variation in frogs' conspicuousness, body size and toxicity, but not in diet specialization or jumping performance. Body size was positively correlated with conspicuousness among localities and all individuals, but not within each locality. Jumping performance was positively correlated with conspicuousness among all individuals and within each locality, but not among localities. Interestingly, toxicity was not correlated with conspicuousness, but when excluding frogs from locality CP6 (ten times more toxic than frogs from other localities), we found a negative correlation between conspicuousness and toxicity. The pattern indicates that, in the initial steps of evolutionary divergence, high toxicity stimulates predator learning in less conspicuous localities, a hypothesis deserving further experimental testing. Our results also show that traits defining aposematic syndrome at the intra-specific level do not follow the same correlations at the inter-specific comparisons, suggesting different degrees of evolutionary canalization or heritable variation among studied traits.